Photooxidative-extractive deep desulfurization of diesel using Cu-Fe/TiO2 and eutectic ionic liquid - Mohd Zaid, H.F. (Elsevier Ltd, 2015)
An efficient photooxidative-extractive system for deep desulfurization of model fuel and actual diesel fuel was explored. A series of bimetallic Cu-Fe/TiO2 photocatalysts was synthesized using sol-gel hydrothermal method and characterized using thermogravimetric analysis (TGA), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) coupled with energy dispersive X-ray analysis (EDX), high resolution transmission electron microscopy (HRTEM) and diffuse reflectance UV-visible spectroscopy (DR-UV-Vis). The photocatalysts were evaluated for photooxidative-extractive deep desulfurization of model oil (100, 300 and 500 ppm dibenzothiophene in dodecane) and actual diesel fuel. 2.0 wt Cu-Fe/TiO2 photocatalyst was identified as the most efficient photocatalyst for the conversion of sulfur species under mild conditions in the presence of hydrogen peroxide (H2O2:S molar ratio of 4) as oxidant and eutectic based ionic liquid as extractant. The sulfur conversion in both model oil and actual diesel fuel reached 100. The removal of sulfur species from both model oil and actual diesel fuel was done by two times extraction with a removal of 97.06 and 78.93, respectively in the first run and 2.94 and 21.07, respectively in the second run. The photocatalyst was able to be recycled for six cycles with an average performance of 99.75. Â© 2015 Elsevier Ltd. All rights reserved.